Global research trends in obesity-related asthma (2004–2023): a bibliometric analysis - Lang, Liye; Ma, Mingxuan; Zhao, Hui; Zhang, Jialin; Liu, Sheng; Liu, Hua (Frontiers in Nutrition, 2025)
BackgroundIn recent years, an increasing body of evidence has revealed a complex interplay between obesity and asthma, prompting academic and medical communities to intensify their focus on this area of research. The objective of this study is to undertake a comprehensive bibliometric analysis of the research literature pertaining to obesity-related asthma from 2004 to 2023. This analysis aims to provide precise and valuable insights, as well as to systematically reflect upon the current status and emerging trends within the field.MethodsLiterature data on obesity and asthma research was sourced from the Web of Science Core Collection database. CiteSpace and VOSviewer were utilized to visually analyze bibliometric indicators such as co-authorship, citation networks, and publication frequency of the data to facilitate the identification of patterns and trends.ResultsA total of 3,118 papers were included in the analysis, encompassing 2,539 articles and 579 reviews. Throughout the last 20 years, the volume of publications has shown a consistent upward trend. The United States and Harvard University are at the forefront of this research field. Professor Dixon Anne E. is recognized as a pioneer and leading figure in the cultivation of obesity-related asthma research. Keyword analysis identified topics such as “childhood asthma,” “bariatric surgery,” “physical activity,” “gut microbiota,” “COVID-19,” “food allergy,” “asthma control,” “nutrition examination,” and “severe asthma.”ConclusionThe research domain of obesity-related asthma has experienced a substantial growth, with the United States, the United Kingdom, and China leading the global landscape. The focus on asthma in obese adolescents and children, the role of bariatric surgery, and lifestyle interventions remains a consistent area of interest, with considerable potential for further study. These findings provide a scientific basis for the development of personalized treatment programs for obese asthma patients. In addition, this study highlights the importance of further research in the fields of gut microbiota, COVID-19, and food allergy, providing directions for future policymaking.